2012
DOI: 10.1089/apc.2012.0208
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Determinants of Condom Use Among HIV Clients in Uganda

Abstract: Little research has examined gender differences in reporting of condom use, which is the goal of our analysis. A baseline study was conducted in two urban clinics and we examined data from sexually active clients entering HIV care who enrolled in a prospective longitudinal cohort study. The primary outcome was consistent condom use and determinant variables were demographics, physical health and immune status, economic well-being, relationship characteristics, psychosocial functioning, and self-efficacy. Of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Results of this study revealed that except for participants with healthy husbands (HIV negative), other participants were not constantly using condoms. Various studies also revealed that one quarter to three quarters of women with HIV were not constantly using condoms for sexual intercourse ( Ayiga, 2012 ; Chakrapani, Newman, Shunmugam, & Dubrow, 2010 ; Walusaga, Kyohangirwe, & Wagner, 2012 ). Obstacles in the way of using condoms in this research were the unwillingness of males to use condom (due to a reduction in sexual desire), the belief in ineffectiveness of condom, and lack of disclosure of HIV status (as a result of a lack of responsiveness) to one’s sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study revealed that except for participants with healthy husbands (HIV negative), other participants were not constantly using condoms. Various studies also revealed that one quarter to three quarters of women with HIV were not constantly using condoms for sexual intercourse ( Ayiga, 2012 ; Chakrapani, Newman, Shunmugam, & Dubrow, 2010 ; Walusaga, Kyohangirwe, & Wagner, 2012 ). Obstacles in the way of using condoms in this research were the unwillingness of males to use condom (due to a reduction in sexual desire), the belief in ineffectiveness of condom, and lack of disclosure of HIV status (as a result of a lack of responsiveness) to one’s sexual partner.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Rates of consistent condom use also vary by gender, with men reporting higher rates than women. 36,37 Negotiating condom use is particularly difficult for women who have not disclosed their HIV status to their partners. 19,38 These studies highlight the need to offer PLHIV prevention messages and services in order to reduce HIV risk behavior among this population.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the evidence appointed in a study that involved 508 male and female participants in Uganda. When comparing the consistent condom use between men and women, the score for men was 48.1%, against 31.8% for women 14 . This difference according to sex involves cultural aspects, as men are stimulated early to have sexual relations, while women are discouraged.…”
Section: Discussionmentioning
confidence: 95%